Meningkatkan Aktivitas Belajar Siswa dengan Memanfaatkan Information and Communications Technology (ICT) pada Materi Penyajian Data di Kelas IX SMPN 5 Sabang - Irawati Irawati (Didaktik Matematika, 2015)
Abstract. Learning with ICT can produce new works that an indigenous, has a high value, and more meaningful. The purpose of this research was to improve student learning outcomes IX grade SMP Negeri 5 Sabang on the topic of data display through ICT-based learning. The subjects were students of class IX of the number of students 18 people. This research was a classroom action research (PTK), which consists of two cycles with the phases of planning, action, observation, and reflection. Based on the results of research and data analysis can be concluded that students completenessthe goal individually in which the first cycle as many 9% and the second cycle as many 15%. The most dominant teachersactivity in the second cycle was to guide students in conducting discussions, while most dominant students activity was a discussion about the problems submitted by teachers. In this case, the ability of teachers to manage learning using ICT has increased from the category of good to be very good.Keywords: ICT, student learning outcomes, teacher activity, student activities